Pengaruh Latihan Bicep curl dan Preacher curl Terhadap Kemampuan Tangkapan Satu Kaki Olahraga Gulat Mahasiswa STKIP YPUP Makassar - Akbar Yusuf; Andi Sahrul Jahrir (Jendela Olahraga, 2020)
Effects of Bicep curl and Preacher curl Exercises on Capability of One Leg Wrestling STKIP YPUP Makassar StudentThis study aims to determine the effect of bicep curl exercises on the ability to catch one foot of STKIP YPUP Makassar students, to determine the effect of preacher curl training on the ability to catch one foot of STKIP YPUP Makassar students and to determine the difference in effect between bicep curl and preacher curl Makassar STKIP YPUP student feet. This research method is a kind of experimental research which was chosen randomly and then given a pretest with a population of all STKIP YPUP students who have programmed 30 wrestling courses and then divided into two groups using ordinal paired maching. data analysis techniques used t test with a significance level of 0.05. The results of this study show that there is a significant influence on the bicep curl exercise group with an average increase of 10,800 with a significant level of 0.05. There was a significant influence on the preacher curl training group with an average increase of 12.733 with a significant level of 0.05. There is a difference in effect between bicep curl and preacher curl exercises by showing the difference or difference in mean values of 1,933. thus showing the preacher curl training group has a very good effect compared to the bicep curl.Keywords: Bicep curl, preacher curl, wrestling and one foot catch, experimentPenelitian ini bertujuan untuk mengetahui pengaruh latihan bicep curl terhadap kemampuan tangkapan satu kaki mahasiswa STKIP YPUP Makassar, untuk mengetahui pengaruh latihan preacher curl terhadap kemampuan tangkapan satu kaki mahasiswa STKIP YPUP Makassar dan untuk mengetahui perbedaan pengaruh antara latihan bicep curl dan preacher curl terhadap kemampuan tangkapan satu kaki mahasiswa STKIP YPUP Makassar. Metode penelitian ini merupakan jenis penelitian eksperimen yang dipilih secara random purposive kemudian diberi pretest dengan populasi semua mahasiswa STKIP YPUP yang telah memprogramkan mata kuliah gulat yang jumlahnya sebanyak 30 orang mahasiswa kemudian dibagi menjadi dua kelompok dengan menggunakan maching ordinal paired. teknik analisis data yang digunakan uji t dengan taraf signifikan 0.05. Hasil penelitian ini menujukkan ada pengaruh yang signifikan kelompok latihan bicep curl dengan peningkatan rata rata 10,800 dengan taraf signifikan 0,05. Ada pengaruh yang signifikan kelompok latihan preacher curl dengan peningkatan rata rata 12,733 dengan taraf signifikan 0,05. Ada perbedaan pengaruh antara latihan bicep curl dan preacher curl dengan menunjukkan perbedaan atau selisih nilai rata rata 1,933. sehingga menunjukkan kelompok latihan preacher curl memiliki pengaruh yang sangat baik dibanding bicep curl.Kata kunci: bicep curl, preacher curl, gulat dan tangkapan satu kaki, eksperimen